Ameloblastic carcinoma of the maxilla: A case report - Campos Franca, Diurianne Caroline [UNESP]; Moreira, Joao Milanez; Coelho Avila de Aguiar, Sandra Maria Herondina; De Carvalhos, Artur Aburad; Goiato, Marcelo Coelho [UNESP] (Spandidos Publ Ltd, 2012)
This study aims to present the clinical features and treatment of a case of maxillary ameloblastic carcinoma. A meloblastic carcinoma is a rare malignant odontogenic carcinoma that has metastatic potential. Due to its rare incidence, there are few studies focusing on its radiological characteristics. When ameloblastic carcinoma demonstrates an aggressive appearance, it may be diagnosed as a malignant tumor; however, in cases showing a non-aggressive appearance, it is difficult to distinguish ameloblastic carcinoma from ameloblastoma. We report a case of ameloblastic carcinoma of the maxilla in a 59-year-old male patient, including the clinical signs, radiological images and pathological features. A partial area was surgically excised under local anesthesia and the material was sent to the Laboratory of Oral Pathology. The histological sections revealed a fragmented odontogenic tumor of epithelial origin, consisting of solid parenchyma and also revealed basal cells resembling ameloblasts, occasionally arranged in palisades. Certain parts of the architecture resembled that of an ameloblastoma; however, the cytology of other areas confirmed the diagnosis of ameloblastic carcinoma of the maxilla. The patient was scheduled for definitive surgery, including a right maxillectomy and radiotherapy. The patient was followed up every 3 months. After 2 years follow-up, there were no clinical or radiological signs of recurrence.
Keywords: ameloblastic carcinoma; maxilla; surgery; oral; case report